2013
DOI: 10.1096/fj.13-232272
|View full text |Cite
|
Sign up to set email alerts
|

The endolysosomal cysteine cathepsins L and K are involved in macrophage‐mediated clearance of Staphylococcus aureus and the concomitant cytokine induction

Abstract: Cysteine cathepsins are endolysosomal cysteine proteases highly expressed in macrophages; however, their individual contributions to the elimination of bacteria and bacteria-induced cytokine production by macrophages are unknown. We assessed the contribution of cysteine cathepsins to macrophage defense pathways against Staphylococcus aureus by using chemical inhibitors and by infecting primary bone marrow-derived macrophages deficient in 1 of 7 major macrophage-expressed endolysosomal cysteine proteases. We sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 61 publications
4
39
0
Order By: Relevance
“…It is not clear whether tick serpins rely on their protease inhibitory activities to regulate the host immune response or not. Muller and colleagues reported that Cathepsins L and K are critical for cytokine production from S. aureus ‐infected macrophages . Our data also suggested that Cathepsins B and G are required for sufficient activation of mouse macrophage by LPS stimulation.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…It is not clear whether tick serpins rely on their protease inhibitory activities to regulate the host immune response or not. Muller and colleagues reported that Cathepsins L and K are critical for cytokine production from S. aureus ‐infected macrophages . Our data also suggested that Cathepsins B and G are required for sufficient activation of mouse macrophage by LPS stimulation.…”
Section: Discussionsupporting
confidence: 70%
“…Cathepsin B was required for optimal posttranslational processing and production of TNF‐α in response to lipopolysaccharide (LPS) . Mice deficient in the serine protease Cathepsin L are much more susceptible to lethal Staphylococcus aureus infection than wild‐type mice . Whether arthropod‐derived serpins regulate host immune responses via their protease inhibitory functions has not been discussed in the previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…The assay was performed as previously described (Muller et al, 2014). In brief, macrophages plated in 24 well plates were infected with MRSA (MOI 10) grown in antibiotics overnight.…”
Section: Methodsmentioning
confidence: 99%
“…However, the main focus of research was for a long time on the ubiquitously expressed cathepsins B, D, and L. In contrast, the cysteine cathepsins K and S gained attention only more recently (Arampatzidou et al 2012;Dauth et al 2012;Driessen et al 1999;Friedrichs et al 2003;Muller et al 2014;Pierre and Mellman 1998;Tamhane et al 2014;Tepel et al 2000). This is because of their cell type-specific expression and vital functions, for instance, in the pericellular space (resorption lacuna) of osteoclasts or in the extracellular space Fig.…”
Section: Endo-lysosomal Cysteine Peptidases From a Canonical Perspectivementioning
confidence: 99%